Project-Based Learning and Self-Efficacy as Predictors of Students’ Motivation in Aqidah Learning - Nur Mubin; Nur Fikriyatul Hasanah (Ar-Fachruddin: Pendidikan Agama Islam, 2025)
Research Objective – This study aimed to examine the predictive influence of Project-Based Learning (PjBL) and self-efficacy on students’ learning motivation in the subject of aqidah at the Madrasah Ibtidaiyah level. The research was designed to bridge pedagogical innovation and psychological constructs, thereby providing a comprehensive understanding of factors that shape motivation in Islamic primary education. Methodology – A quantitative correlational design was employed with 60 fifth-grade students from Madrasah Ibtidaiyah Daruttaqwa Suci Gresik. Data were collected through three stages: observation checklists measuring the fidelity of PjBL implementation, questionnaires on self-efficacy and motivation adapted from validated instruments, and short reflective teacher interviews to confirm classroom practices. All instruments demonstrated acceptable reliability (Cronbach’s alpha > 0.70). Multiple regression analysis using SPSS version 26 was conducted to test the predictive relationships, following assumption checks for normality, linearity, and multicollinearity. Findings – Results indicated that students reported high levels of PjBL implementation (M = 4.12), moderate-to-high self-efficacy (M = 3.89), and strong learning motivation (M = 4.21). Correlation analysis revealed significant positive associations among all variables, with self-efficacy demonstrating the strongest correlation with motivation (r = .62, p < .01). Regression analysis confirmed that PjBL and self-efficacy jointly explained 52% of the variance in learning motivation, with self-efficacy (β = 0.46, p < .001) emerging as a stronger predictor than PjBL (β = 0.34, p < .01). Research Implications/Limitations – The findings highlight the need to integrate student-centered pedagogies with strategies that strengthen learners’ self-belief. However, the study’s focus on a single school and cross-sectional design limits generalizability. Originality/Value – This study contributes to the limited literature on Islamic education by demonstrating the universal role of self-efficacy and the value of combining innovative pedagogy with psychological empowerment to enhance learning motivation.